Neural plasticity and regeneration - Seil, Fredrick J (Elsevier, 2000)
While a cure for spinal cord injury remains elusive, the contents of this volume convey a sense of progress towards this goal. More has been learned about the primary and secondary consequences of spinal cord injury and more is being understood about recovery mechanisms that are intrinsic to the nervous system and that might be further encouraged. Expanding the control capacity of uninjured portions of the nervous system may be one approach to improving the functional capabilities of those afflicted with this disorder. New therapies in the form of transplantable cells that can encourage growth or myelination or prevent secondary damage or that can substitute for injured cells appear promising for future applications. Genetic and tissue engineering studies give us further hope, and under continuous development are novel drugs with greater specificity and fewer detrimental effects and improved delivery methods for such drugs. The volume is organized into six topic sections, including I) Strategies for Spinal Cord Injury Repair, II) Plasticity of the Injured Spinal Cord: Retraining Neural Circuits to Promote Motor Recovery, III) Impact of Neuroprosthetic Applications on Functional Recovery, IV) Neurotrophins and Activity-Dependent Plasticity, V) Candidate Cells for Transplantation into the Injured CNS and VI) New Directions in Regeneration Research. Both clinical and experimental animal studies are presented in the first three sections, while predominantly basic research is the focus of the second half of the book.
Progress in brain research ; vol. 128
Keywords: neurovědy; neuroplasticita; Neuronal Plasticity; regenerace; Regeneration; neurologie